Digital Badge Metadata: A Case Study in Quality Assurance - Jonathan Lau (Journal of Innovation in Polytechnic Education)
Digital badges are competency-based credentials that provide specific information within the metadata. However, there appears to be no research investigating the quality of the information conveyed in the metadata. To better understand how to convey the value of digital badges, this study investigated the quality of the metadata. This study used mixed-method content analysis on the digital badges developed in a micro-certification pilot project. The results revealed the similarities and differences between the metadata, as well as the quality conveyed. This study found that metadata information's type and location may affect the perceived value of digital badges. Building on the research of digital badge quality assurance, this study suggests developing standards for the metadata.